Analisis Penggunaan Material Batu Dari Desa Tanjung Jariangau Kabupaten Kotawaringin Timur Sebagai Agregat Pada Campuran Hot Rolled Sheet-Base (Hrs-Base) - Jepri Kurniawan; Salonten; Okta Meilawaty (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
The use of stone material from Tanjung Jariangau Village as an aggregate in the Hot Rolled Sheet Base (HRS-Base) mi. It is a form of optimal use of natural resources, therefore there is a need for efforts to equip natural resources around. Tanjung Jariangau Village, Mentaya Hulu District, East Kotawaringin Regency, Central Kalimantan Province has natural resources in the form of stones that have not been properly utilised. The study was conducted to analyse the use of stones from Tanjung Jariangau Village as aggregates in the Hot Rolled Sheet Base (HRS-Base) mi. It is hoped that the stone material from Tanjung Jariangau Village can provide a solution to the need for HRS base materials in Central Kalimantan, especially in the surrounding area. Research will be carried out in the laboratory, physical properties in aggregates will be eamined to the Marshall test. The calculation results from the Marshall test obtained optimum asphalt content (KAO) of 6.02%, stability of 922.284 kg, inter-aggregate voids (VMA) of 18.372%, voids in the mi (VIM) of 4.357%, voids filled with asphalt (VFA) of 78.168% and Marshall quotient (MQ) of 278.259 kg/mm.